1992
DOI: 10.1246/cl.1992.1847
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Chlorophylls a and a′ in the Intermolecular Association Behavior. Visible Absorption and Circular Dichroism Spectral Features in Aqueous Methanol

Abstract: Visible absorption and circular dichroism (CD) spectroscopies on a series of chlorophyll (Chl) a/a′ epimeric mixtures in aqueous methanol have unraveled a striking influence of the stereochemistry at carbon 132 on the mode of intermolecular association of these pigments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 7 publications
1
10
0
Order By: Relevance
“…The mass spectrum of #2 was the same as that of #1 ( m / z 683.3 for [ M +H] + ), so #2 should be the isomer of #1. The visible and circular dichroism spectra of bands #1 and #2 (Figure S1) unambiguously indicated that band #2 was that of the C13 2 ‐epimer, Zn‐ 1 c′ , of Zn‐ 1 c (#1), upon comparison with reported data . Additionally, the fact that the 13 2 R forms of Chl a and its analogues moved faster than that of the corresponding 13 2 S form in RP‐HPLC analysis supports the assignment of #2 as prime form Zn‐ 1 c′ .…”
Section: Resultssupporting
confidence: 68%
“…The mass spectrum of #2 was the same as that of #1 ( m / z 683.3 for [ M +H] + ), so #2 should be the isomer of #1. The visible and circular dichroism spectra of bands #1 and #2 (Figure S1) unambiguously indicated that band #2 was that of the C13 2 ‐epimer, Zn‐ 1 c′ , of Zn‐ 1 c (#1), upon comparison with reported data . Additionally, the fact that the 13 2 R forms of Chl a and its analogues moved faster than that of the corresponding 13 2 S form in RP‐HPLC analysis supports the assignment of #2 as prime form Zn‐ 1 c′ .…”
Section: Resultssupporting
confidence: 68%
“…The peak heights in both regions were reduced by roughly 40% compared with those of Chl a' monomer in methanol. There was almost no absorption tailing into the near IR region, in contrast with a Chl a' aggregate at M 60% (17). The most characteristic feature in Fig.…”
Section: Methodsmentioning
confidence: 87%
“…3). The conservative components are very intense: their amplitudes for a 4.95 k*.M solution (monomer base concentration) were +288 mdeg (694 nm) and -275 mdeg (715 nm), which was roughly 100-fold larger than the Q, signal of monomeric Chl a' in methanol (17). The band widths (FWHM) were 260 cm-' (694 nm) and 245 cm-I (715 nm).…”
Section: Absorption and CD Spectra Of Chl A' Aggregate At Stationary mentioning
confidence: 92%
“…This has a historical reason as Oba was involved in the first demonstration that in PS I the Chl a¢ epimer (i.e. with reverse orientation of the 13 2 -carbomethoxy group) is present and has extensively studied the spectral differences between the two Chl a epimers (Watanabe et al 1992). In some BChls, as in pyrochlorophyllides, the 13 2 -carbomethoxy group is absent.…”
Section: Introduction and A Note On Nomenclaturementioning
confidence: 99%